The next great war? : the roots of World War I and the risk of U.S.-China conflict - Rosecrance, Richard N.; Miller, Steven E. (Cambridge, Massachusetts : The MIT Press, 2014)
Experts consider how the lessons of World War I can help prevent U.S.--China conflict.
Introduction : The Sarajevo Centenary, 1914 and the Rise of China / Steven E. Miller -- Before the War : Three Styles of Diplomacy / Alan Alexandroff -- Respites or Resolutions? : Recurring Crises and the Origins of War / Arthur A. Stein -- Better Now Than Later : The Paradox of 1914 as Everyone's Favored Year for War / Jack Snyder -- Allies, Overbalance, and War / Richard N. Rosecrance -- Economic Interdependence and War / Richard N. Cooper -- The Thucydides Trap / Graham Allison -- Thucydides Dethroned : Historical Differences That Weaken the Peloponnesian Analogy / David K. Richards -- Thucydides, Alliance Politics, and Great Power Conflict / Charles S. Maier -- War, Revolution, and the Uncertain Primacy of Domestic Politics / T.G. Otte -- Domestic Coalitions, Internationalization, and War : Then and Now / Etel Solingen -- European Militaries and the Origins of World War I / Stephen Van Evera -- Inevitability and War / Joseph S. Nye Jr. -- Lessons from Europe 1914 for Asia 2014 : Reflections on the Centenary of the Outbreak of World War I / Kevin Rudd -- Contingency as a Cause (or Little Things Mean a Lot) / Richard N. Rosecrance.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: World War, 1914-1918 -- Causes; United States -- Foreign relations -- China; China -- Foreign relations -- United States; Guerre mondiale, 1914-1918 -- Causes; États-Unis -- Relations extérieures -- Chine; Chine -- Relations extérieures -- États-Unis.; HISTORY -- Europe -- Western; Diplomatic relations; War -- Causes; China; United States; 1914-1918; SOCIAL SCIENCES/Political Science/General; HUMANITIES/History; SOCIAL SCIENCES/Political Science/International Relations & Security